Study of the Static and Dynamic Nuclear Properties and Form Factors for Some Magnesium Isotopes 29-34 Mg - lubna abduljabbar mahmood; Gaith Naima Flaiyh (Iraqi Journal of Physics, 2021)
Nuclear structure of 29-34Mg isotopes toward neutron dripline have been investigated using shell model with Skyrme-Hartree–Fock calculations. In particular nuclear densities for proton, neutron, mass and charge densities with their corresponding rms radii, neutron skin thicknesses and inelastic electron scattering form factors are calculated for positive low-lying states. The deduced results are discussed for the transverse form factor and compared with the available experimental data. It has been confirmed that the combining shell model with Hartree-Fock mean field method with Skyrme interaction can accommodate very well the nuclear excitation properties and can reach a highly descriptive and predictive power when investigating different nuclear configurations of stable and unstable nuclei.